The Protection of Foreign Investments in Disputed Maritime Areas of The South China Sea - Nguyen, Anh (UI Scholars Hub, 2021)
This study used a legal framework developed by a recent scholarship to examine the protection of foreign investments in disputed maritime areas. The framework classifies these areas and establishes the jurisdictional challenges faced by investment tribunals in such constellations. For instance, there are high-profile foreign investments in the South China Sea (SCS) with significant threats of increasing escalation between SCS states. Therefore, this study aimed to examine investment protection in disputed waters of SCS using this framework. Since BITs of SCS states include maritime areas beyond the territorial sea in their territories, there is need to abide to international law. Therefore, tribunals are caught in a double bind when deciding on their jurisdiction. For instance, they need to assess whether disputed maritime areas fall under the BIT’s territorial scope of protection, conferring them to territorial jurisdiction. This necessitate the need to determine the maritime entitlements conformity with international law, which is against the scope of jurisdiction of the investment tribunal. The results showed that tribunals may not overcome this jurisdictional hurdle as a matter de lege lata. In this regard, de lege feranda are promising legal rationales to establish incidental jurisdiction over disputed maritime areas. Therefore, tribunals decide on their jurisdiction over investments in these areas.